The Impact of Enterprise 2.0 on SMEs - Antunes, D.; Isaias, Pedro (IGI Global, 2014)
Enterprise 2.0 has been part of the business sector vocabulary for quite some time now. Web 2.0's revolutionary philosophy and applications have been absorbed by various areas of society. The success of the business sector benefits from a client-oriented approach, so when the benefits of a user-centric Web became evident, adopting it was the natural next step. Enterprise 2.0 presents advantages mainly in two areas: within organizations, as they enable communication through new dynamic methods of communication and interaction, in order to enhance efficiency and productivity; and between companies and customers, suppliers, and partners, as they increase both revenue and customer satisfaction and promote cooperation and co-creation to improve services or products. This chapter illustrates the reality of Small and Medium Enterprises' (SMEs) adoption of Web 2.0. An online questionnaire was developed to assess numerous SMEs in Portugal to understand if and how Web 2.0 implementation is taking place.